Yellow mealworm (Tenebrio Molitor) enhances intestinal immunity in largemouth bass (Micropterus salmoides) via the NFκB/survivin signaling pathway. Issue 136 (May 2023) - Ge, Chunyu; Liang, Xiaofang; Wu, Xiaoliang; Wang, Jie; Wang, Hao; Qin, Yuchang; Xue, Min
Abstract: This study aimed to elucidate the mechanisms of yellow mealworm ( Tenebrio Molitor, YM) in intestinal immunity and health. Largemouth bass, as an enteritis modeling animal, were fed 3 diets containing YM at 0% (YM0), 24% (YM24) and 48% (YM48). The YM24 group had reduced levels of proinflammatory cytokines, while the YM48 group experienced a negative impact on intestinal health. Next, the Edwardsiella tarda ( E. tarda ) challenge test consisted of 4 YM diets, 0% (EYM0), 12% (EYM12), 24% (EYM24), and 36% (EYM36). The EYM0 and EYM12 groups exhibited intestinal damage and immunosuppression by the pathogenic bacteria. However, the above adverse phenotypes were attenuated in the EYM24 and EYM36 groups. Mechanistically, the EYM24 and EYM36 groups enhanced intestinal immunity in largemouth bass via activating NFκBp65 and further upregulating survivin expression to inhibit apoptosis. The results identify a protective mechanism of YM as a novel food or feed source by improving intestinal health. Highlights: A dietary content of 24% yellow mealworm ( Tenebrio Molitor, YM) reduces the proinflammatory cytokines responses. Dietary contents of 0% and 12% YM exhibited fish intestinal damage and immunosuppression after  Edwardsiella   tarda  challenge. Dietary contents of 24% and 36% reversed the pathological adverse effects after  Edwardsiella   tarda  challenge.Dietary contents of 48% of YM negatively affects gut health and microbiota. YM relieves intestinal damage by enhancing the activation of the NFκB/survivin signaling pathway.